2014
DOI: 10.1002/chem.201404004
|View full text |Cite
|
Sign up to set email alerts
|

Alkali‐Metal Ion Catalysis and Inhibition in SNAr Displacement: Relative Stabilization of Ground State and Transition State Determines Catalysis and Inhibition in SNAr Reactivity

Abstract: We report here the first observation of alkali-metal ion catalysis and inhibition in SNAr reactions. The plot of kobsd versus [alkali-metal ethoxide] exhibits downward curvature for the reactions of 1-(4-nitrophenoxy)-2,4-dinitrobenzene with EtOLi, EtONa, and EtOK, but upward curvature for the corresponding reaction with EtOK in the presence of 18-crown-6-ether (18C6). Dissection of kobsd into the second-order rate constants for the reactions with the dissociated EtO(-) and the ion-paired EtOM (i.e., k EtO - a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…It is well known that S N Ar reactions proceed through a stepwise mechanism with a Meisenheimer complex, in which the RDS is dependent on reaction conditions. For example, we have recently reported that S N Ar reactions of 1‐(Y‐substituted‐phenoxy)‐2,4‐dinitrobenzenes with C 2 H 5 O − in anhydrous ethanol proceed through an anionic Meisenheimer complex, in which expulsion of the leaving group occurs after the RDS 16a . In contrast, we have shown that S N Ar reactions of the same substrates with secondary amines proceed through a stepwise mechanism with a zwitterionic Meisenheimer complex in which expulsion of the leaving group occurs at the RDS 16b …”
Section: Resultsmentioning
confidence: 99%
“…It is well known that S N Ar reactions proceed through a stepwise mechanism with a Meisenheimer complex, in which the RDS is dependent on reaction conditions. For example, we have recently reported that S N Ar reactions of 1‐(Y‐substituted‐phenoxy)‐2,4‐dinitrobenzenes with C 2 H 5 O − in anhydrous ethanol proceed through an anionic Meisenheimer complex, in which expulsion of the leaving group occurs after the RDS 16a . In contrast, we have shown that S N Ar reactions of the same substrates with secondary amines proceed through a stepwise mechanism with a zwitterionic Meisenheimer complex in which expulsion of the leaving group occurs at the RDS 16b …”
Section: Resultsmentioning
confidence: 99%
“…A quantity of the half-coupled product 9 was also formed. A front-running compound 10 13 was also formed in variable but significant quantities and was characterised by its proton and carbon NMR spectra. This known compound forms here by the displacement of fluorine with ethanol in the hot solution.…”
Section: Discussionmentioning
confidence: 99%
“…The term sh means shoulder. 1 H and 13 C nuclear magnetic resonance (NMR) spectra were recorded at 400 and 100.5 MHz, respectively, using a Varian 400 spectrometer. Chemical shifts, δ, are given in ppm and using a solvent peak as an internal reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…anionic versus neutral and; the effect of solvent. [1][2][3][4] Our interests have included studies of S N Ar reactions of highly reactive, α-nucleophiles, 33,34 effects of alkali metal ions, 35 reactions of primary and secondary cyclic amines [24][25][26] with Sanger's reagent (1-fluoro-2,4dinitrobenzene), a series of 1-halo-2,4-dinitrobenzenes and with 1-(substituted phenoxy)-2,4dinitrobenzenes as electron deficient substrates, usually in acetonitrile (MeCN) solvent often with comparison to the results in water, as a standard reaction medium. Nucleophilic reaction of amines in the S N Ar process is traditionally described, 36 as shown in Scheme 1, as a partition between two pathways after formation of the initial zwitterionic MC, i.e., MC ± ; expulsion of the leaving group, a substituted phenoxide (ArO -) in current work, gives the protonated product, PH + , that equilibrates rapidly to give the observed 2,4dinitroaniline product, P (Scheme 1) in the basic medium.…”
Section: R a F Tmentioning
confidence: 99%